Novel Scaffolds Fabricated Using Oleuropein for Bone Tissue Engineering - Fan, Hui (Hindawi Publishing Corporation, 2014)
We investigated the feasibility of oleuropein as a cross-linking agent for fabricating three-dimensional (3D) porous composite scaffolds for bone tissue engineering. Human-like collagen (HLC) and nanohydroxyapatite (n-HAp) were used to fabricate the composite scaffold by way of cross-linking. The mechanical tests revealed superior properties for the cross-linked scaffolds compared to the uncross-linked scaffolds. The as-obtained composite scaffold had a 3D porous structure with pores ranging from 120 to 300 μm and a porosity of 73.6 ± 2.3%. The cross-linked scaffolds were seeded with MC3T3-E1 Subclone 14 mouse osteoblasts. Fluorescence staining, the Cell Counting Kit-8 (CCK-8) assay, and scanning electron microscopy (SEM) indicated that the scaffolds enhanced cell adhesion and proliferation. Our results indicate the potential of these scaffolds for bone tissue engineering.